Uma política de investimentos defensiva para o resultado operacional de hospitais públicos na presença de filas e de desigualdades de acesso a hospitais privados - Alexandre Marinho; Simone de Souza Cardoso; Vivian Vicente de Almeida (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– This work develops a framework able to guide investment in hospital capacities within the realm of a complex health system. The study is performed from the standpoint of the economic surplus of public hospitals. Although the paper is inspired by the Brazilian National Health System, it can be useful to many others situations where public and private hospital share the market. The adoption of a public market share, the presence of a stochastic demand, the addressing of waiting times, and the institution of punishment for insufficient supply are interesting features of the paper.
Keywords: I18; H51; H54; L33; 330